Hybrid Trauma Management: Is It the Way We Are Heading? - Paran, Maya; Kessel, Boris (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Background: Hybrid trauma management, namely the combination of open and endovascular techniques and/or the application of endovascular methods in the operating/emergency room, is a quickly growing concept worldwide. However, its implications are not well established. We aimed to review the current data regarding hybrid trauma management in medical literature. Methods: A review of the medical literature published between 2000 and 2020 using PubMed, Cochrane, Embase and Medline databases was performed in search of clinical studies regarding hybrid trauma treatments. Case-reports were excluded from this review. The manuscripts were analyzed regarding the mechanism, location, and type of injury, endovascular and surgical techniques utilized, and the outcome. Results: In total, 14 studies reporting hybrid trauma management in a total of 1,049 patients met the inclusion criteria and were analyzed. Blunt trauma was the leading trauma mechanism (87.1%) and the most common procedure was transcatheter arterial embolization, performed in 29.7% of patients. The overall mortality was 15.2%. Regarding case-control studies, 85.7% have shown hybrid trauma management to be associated with a shorter time from arrival to intervention, 42.9% reported lower rates of unfavorable outcome, and 28.6% reported reduced requirement for red blood cell transfusion as compared with conventional management. Conclusions: Accumulating data suggests that hybrid management may be associated with a shorter time from arrival to intervention, lower rates of unfavorable outcomes and a reduced requirement for red blood cell transfusion as compared with conventional management of trauma patients.